1994
DOI: 10.1080/01140671.1994.9513847
|View full text |Cite
|
Sign up to set email alerts
|

Field performance of transgenic potatoes

Abstract: Field performance was assessed in 13 transgenic potato (Solanum tuberosum L.) lines from three cultivars expressing a selectable marker gene conferring kanamycin resistance. All lines developed unexpected changes in the phenotypic appearance of shoots, and/or poor tuber yield generally involving a reduced number of small tubers. Each independently selected transgenic line showed distinctly different changes in phenotypic appearance or yield performance. The observed changes were very uniform within each clonal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 35 publications
0
31
0
1
Order By: Relevance
“…Several metabolic studies on transgenic plants have been reported and revealed unanticipated effects of genetic transformation (Haslberger 2003) in potato (Conner et al 1994;Birch et al 2002), rice (Momma et al 1999), canola (Shewmaker et al 1999), oilseed rape (Al-Kaff et al 2000), barley (Horvath et al 2001) and maize (Saxena and Stotzky 2001). Regarding bar gene-containing transgenic plants, Al-Kaff et al (2000) reported that oilseed rape plants unexpectedly became sensitive to herbicide FINALE Ò after infection with CaMV.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several metabolic studies on transgenic plants have been reported and revealed unanticipated effects of genetic transformation (Haslberger 2003) in potato (Conner et al 1994;Birch et al 2002), rice (Momma et al 1999), canola (Shewmaker et al 1999), oilseed rape (Al-Kaff et al 2000), barley (Horvath et al 2001) and maize (Saxena and Stotzky 2001). Regarding bar gene-containing transgenic plants, Al-Kaff et al (2000) reported that oilseed rape plants unexpectedly became sensitive to herbicide FINALE Ò after infection with CaMV.…”
Section: Resultsmentioning
confidence: 99%
“…However, side effects of these foreign DNAs in pineapple plants have not been explored to date. It is convenient to note that such side effects are among the major concerns in the today's societies (Schubert 2005) and several metabolic studies on transgenic plants have revealed unanticipated effects of genetic transformation (Conner et al 1994;Momma et al 1999;Shewmaker et al 1999;Al-Kaff et al 2000;Horvath et al 2001;Saxena and Stotzky 2001;Birch et al 2002;Haslberger 2003). These unexpected side effects of transformation have caused a negative impact in the public/market perception about genetically modified plant food (Kuiper et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Putative transgenic plants were transferred back to the multiplication medium containing Timentin only to clonally propagate plants from each independently derived line. Five replicate plants were established for each independently derived line and maintained in a containment greenhouse as previously described (Conner et al 1994). …”
Section: Hindiiimentioning
confidence: 99%
“…This, however, is usually not found in practice. Phenotypic variation is the norm within populations of plants from the same experiment (Hoekema et al, 1989;Conner et al, 1994;Bregitzer et al, 1998;Singh et al, 1998;Kaniewski and Thomas, 1999;Shu et al, 2002) and breeders and researchers must carefully screen numerous transformed plants to obtain one or a few plants which exhibit only the desired traits (Kumar et al, 1998;Dear et al, 2003). Despite this, even plants originally selected as having the appropriate phenotype are often found, during later experiments or commercial use, to have unexpected and unintended traits (Kuiper et al, 2001;Haslberger, 2003).…”
Section: Biotechnology and Genetic Engineeringmentioning
confidence: 99%